Liquid Soap Production from Catfish (Pangasius hypophthalmus) Fat Waste - Nabila Aprianti; Siti Nurhayati; Rosdiana Moeksin (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Catfish (Pangasius hypophthalmus) fat is a waste that has not been used optimally, especially in the use of soap. This study aimed to determine the effect of operating conditions are temperature, reaction time, and the ratio of volume between catfish oil and KOH. Soap can be formed by saponification reaction with strong alkali by hydrolyzing catfish oil with variations in the volume ratio of reactants (1:2, 1:3 and 1:4), temperature (75 °C and 95 °C) and reaction time (45 minutes and 75 minutes) with a constant stirring speed of 300 rpm. In the variation of the volume ratio of reactants, temperature and reaction time carried out in this study, a good liquid soap obtained is the volume ratio of reactants 1:3, temperature 75 °C and reaction time 45 minutes with pH 9.3 and free fatty acid 2.27%. The soap products produced have met SNI No. 06-4085-1996.